Propiedades de explotacion de los agregados para la poda de citricos en Cuba - Paneque Rondon, P.=700 1 Luna Lopez, A.
(Es, En)
Ilus., 4 ref.
Keywords: CITRUS; PODA; CUBA; REVISTA CIENCIAS TECNICAS AGROPECUARIAS